MANAJEMEN QALBU: TELA’AH MA’ANIL HADIS KESEHATAN HATI DAN KESEHATAN MANUSIA - Muhammad Aidil Fitriansyah; Muhajirin Muhajirin; Almunadi Almunadi (El-Sunnah, 2022)
Inside the human chest there is a clot of blood called the heart. So in Arabic it is known as qalb. So in this study examines related to the heart. The purpose of this study is to explain and find out how a healthy heart according to Imam Muslim. Qalb is a way to see the good and bad of human actions. Qalb is an intense language in hadith science circles because the heart is an important thing in human life, including Imam Muslim. So the author raised the theme of Qalb to study more deeply related to the heart. Ma'aanil hadith is a hadith that comes from authentic texts. It aims to carry out an understanding of contextual human life. In this study, contextually, three problems are discussed. the first is about how the concept of the heart in the hadith of Imam Muslim. The second, about how the correlation of physical and non-physical health and how the wisdom of a clean and healthy heart. Meanwhile, in this research, this type of research uses field research. While the data sources used are secondary data sources which consist of a study of books and documentation. Then from the research that the author did about the heart according to the history of Imam Muslim, there are 2 meanings. Qalb is based on the meaning of the heart, and also qalb which means heart. Meanwhile, in a comprehensive sense, the heart is the essence of human beings and determines the good and bad deeds of humans